2016
DOI: 10.1109/jsen.2015.2433836
|View full text |Cite
|
Sign up to set email alerts
|

SiNW-FET in-Air Biosensors for High Sensitive and Specific Detection in Breast Tumor Extract

Abstract: Abstract-The sensitive analysis of proteins is central to disease diagnosis. The detection and investigation of angiogenic and inflammatory ligands in the tumor tissue can further improve the level of knowledge of the cancer disease by capturing the heterogeneity and the complexity of the tumor microenvironment. In previous works we demonstrated that high quality Silicon Nanowire Field Effect Transistors (SiNW-FETs) can be used to sense very low concentration (fM) of pathogenic factors in controlled Phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…In SiNWs the diffusion occurs in the two dimensions perpendicular to the wire (hemicylindrical), which results in a much faster adsorption of analytes [7][8][9] . SiNWs have shown low limits of detection for different biomarkers comprising DNA [10][11][12][13][14] and proteins [2,[15][16][17] in different media including biological fluids [18][19][20][21] and tissues [22,23] . Owing to the well-known nanofabrication methods, and low operational power, Si NW-FETs can be easily integrated into CMOS chips where transducers and necessary circuits for signal processing are integrated on a single chip [2,10,15,24] .…”
Section: Introductionmentioning
confidence: 99%
“…In SiNWs the diffusion occurs in the two dimensions perpendicular to the wire (hemicylindrical), which results in a much faster adsorption of analytes [7][8][9] . SiNWs have shown low limits of detection for different biomarkers comprising DNA [10][11][12][13][14] and proteins [2,[15][16][17] in different media including biological fluids [18][19][20][21] and tissues [22,23] . Owing to the well-known nanofabrication methods, and low operational power, Si NW-FETs can be easily integrated into CMOS chips where transducers and necessary circuits for signal processing are integrated on a single chip [2,10,15,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Although nanowire-based detection of protein cancer markers has clearly evolved from the measurement of purified markers spiked into buffer to the measurement of markers spiked into healthy human serum, a very limited number of studies have quantified these markers in cancer patient blood-derived specimens [27,28]. Along the same lines, to date only two studies have reported the detection of a spiked antigen in cancer patient tissues using antibody-based FET [29,30] or memristor sensors [31]. In these Box 2.…”
Section: Protein Cancer Markersmentioning
confidence: 99%
“…Alternative, smaller bioreceptors. Puppo et al [179] also demonstrated that the biosensing in air was highly sensitive, obtaining femtomolar detection limits for VEGF for complex human breast tumor extracts. Adapted with permission.…”
Section: Alternative Measurement Modesmentioning
confidence: 99%